2016
DOI: 10.3390/molecules21070793
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Novel α-Aminoamides Containing an Indole Moiety for the Treatment of Neuropathic Pain

Abstract: Abstract:The α-aminoamide family of sodium ion channel blockers have exhibited analgesic effects on neuropathic pain. Here, a series of novel α-aminoamides containing an indole ring were designed and synthesized. These compounds were evaluated in mice using a formalin test and they exhibited significant anti-allodynia activities. However, the analgesic mechanism of these compounds remains unclear; a subset of the synthesized compounds can only moderately inhibit the sodium ion channel, Nav1.7, in a whole-cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Their effects on TTX-sensitive activated (TP−1) and inactivated (TP−2) states of Na v 1.7 current were screened at a single dosage (10 μM), based on the IC 50 value (7.10 ± 1.41 μM) of ralfinamide ( Table 3 ). The compounds with the benzimidazole group showed no activity against Na v 1.7, while compounds containing the quinoline group showed modest state-dependent inhibitory potency on Na v 1.7, which is consistent with the result of indole compounds described in the previous study [ 13 ]. The compounds containing the benzofuran group exhibited potent inhibitory activities against Na v 1.7.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Their effects on TTX-sensitive activated (TP−1) and inactivated (TP−2) states of Na v 1.7 current were screened at a single dosage (10 μM), based on the IC 50 value (7.10 ± 1.41 μM) of ralfinamide ( Table 3 ). The compounds with the benzimidazole group showed no activity against Na v 1.7, while compounds containing the quinoline group showed modest state-dependent inhibitory potency on Na v 1.7, which is consistent with the result of indole compounds described in the previous study [ 13 ]. The compounds containing the benzofuran group exhibited potent inhibitory activities against Na v 1.7.…”
Section: Resultssupporting
confidence: 90%
“…Studying the relationship between target selectivity and potency for novel α-aminoamide derivatives is critically needed. Thus, we synthesized a set of novel α-aminoamide derivatives to further investigate the SARs in our previous work [ 13 ]. We confirmed that the chemical moiety of the A ring affected the selectivity to Na v channels and the structure needed to be further modified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6‐Amino‐2,4‐lutidine carboxamides having α‐aminoketone structural motif were designed using 2‐aminopyridine and reported to possess good systemic and topic inflammatory inhibition activities . Antianalgesics were prepared using indole as structural unit and thereafter appending α‐amidoamine moiety on it .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] They have provided an alternative to steroid therapy, which has revealed many problems related to parallel endocrine and metabolic activity, induced osteoporosis and hypercalcemia, as shown by Lessigiarska et al 6 The postponement in treatment causes severe side effects including rhinnorrhoea, rheumatoid arthritis, and atherosclerosis. 7 With their anti-pyretic and analgesic activities, they represent a choice treatment in various inflammatory diseases such as arthritis and rheumatisms.…”
Section: Introductionmentioning
confidence: 99%